Caspase-3 Modulates Regenerative Response After Stroke. (13th January 2014) - Fan, Wenying; Dai, Yiqin; Xu, Haochen; Zhu, Ximin; Cai, Ping; Wang, Lixiang; Sun, Chungang; Hu, Changlong; Zheng, Ping; Zhao, Bing–Qiao
Abstract : Stroke is a leading cause of long-lasting disability in humans. However, currently there are still no effective therapies available for promoting stroke recovery. Recent studies have shown that the adult brain has the capacity to regenerate neurons after stroke. Although this neurogenic response may be functionally important for brain repair after injury, the mechanisms underlying stroke-induced neurogenesis are not known. Caspase-3 is a major executioner and has been identified as a key mediator of neuronal death in the acute stage of stroke. Recently, however, accumulating data indicate that caspase-3 also participates in various biological processes that do not cause cell death. Here, we show that cleaved caspase-3 was increased in newborn neuronal precursor cells (NPCs) in the subventricular zone (SVZ) and the dentate gyrus during the period of stroke recovery, with no evidence of apoptosis. We observed that cleaved caspase-3 was expressed by NPCs and limited its self-renewal without triggering apoptosis in cultured NPCs from the SVZ of ischemic mice. Moreover, we revealed that caspase-3 negatively regulated the proliferation of NPCs through reducing the phosphorylation of Akt. Importantly, we demonstrated that peptide inhibition of caspase-3 activity significantly promoted the proliferation and migration of SVZ NPCs and resulted in a significant increase in subsequent neuronal regeneration and functional recovery after stroke. Together, our data identify a previously unknown caspase-3-dependent mechanism that constrains stroke-induced endogenous neurogenesis and should revitalize interest in targeting caspase-3 for treatment of stroke. Stem Cells 2014;32:473–486